Adaptions in eye-movement behavior during face-to-face communication in noise - Slomianka, Valeska; May, Tobias; Dau, Torsten (Frontiers in Psychology, 2025)
In face-to-face conversations, gaze serves a dual role: it conveys non-verbal messages and facilitates the perception of visual cues that support speech comprehension and smooth turn-taking. Typically, listeners direct their gaze toward the current talker to signal interest in taking the next turn, while talkers monitor listeners for signs of engagement. However, how gaze behavior and its coordination with turn-taking adapt to challenging acoustic environments remains poorly understood. In this study, ten groups of three young, normal-hearing Danish participants engaged in six discussions on several topics, each lasting approximately 7 min. Participants’ eye movements were recorded using Tobii Pro Glasses 3 wearable eye-tracking devices. Conversation difficulty was manipulated by introducing two levels of eight-talker background noise (‘8-talker babble’). Each group participated in three conversations in noise and three in quiet. The analysis revealed that in noisy conditions, participants looked more frequently at their conversational partners and made more eye movements overall. Gaze behavior also became more tightly synchronized with turn-taking: participants showed reduced gaze avoidance at the beginning of their own turns, and both talkers and listeners increasingly oriented their gaze towards the next talker at the end of a turn. These findings indicate that background noise significantly shapes gaze behavior, suggesting an increased reliance on visual information to manage conversational dynamics and comprehend speech. This highlights the critical role of gaze in communication and its potential to inform the design of communication aids and strategies, especially for individuals with communication challenges in noisy environments.